Gyrokinetic turbulence simulation compared with a high ion temperature large helical device experiment - Nunami, M., author; Watanabe, T. H., author; Sugama, H., author; Tanaka, K., author; National Institute for Fusion Science (Toki, Japan : National Institute for Fusion Science, 2011)
PSZJBL